2001
DOI: 10.1680/grim.2001.5.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electrode materials and current intermittence in electro-osmosis

Abstract: The effects of electrode materials and current intermittence on the coefficient of electro-osmotic permeability and the voltage loss at the soil-electrode interfaces are investigated using a marine soil. An electro-osmotic testing cell is designed and fabricated to measure the electro-osmotic induced flow under known boundary conditions. Six pairs of electrodes are tested for the voltage loss at the soil- electrode interfaces and for the coefficient of electroosmotic permeability. The losses in the applied vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(24 citation statements)
references
References 12 publications
2
22
0
Order By: Relevance
“…This decreased the electric resistance of the electrolyte, which in turn increased the electric current and ultimately the temperature. The biggest potential loss in the experiments was observed at the interface of sludge and the graphite anode, consistent with the findings of Mohamedelhassan and Shang [20], who attributed this to the electrochemical potential of the electrode material. Materials with low-electrochemical potential have a low-electrode/electrolyte interface voltage loss.…”
Section: Dewatering and Oil Recovery In The Larger Scale Experimentssupporting
confidence: 90%
“…This decreased the electric resistance of the electrolyte, which in turn increased the electric current and ultimately the temperature. The biggest potential loss in the experiments was observed at the interface of sludge and the graphite anode, consistent with the findings of Mohamedelhassan and Shang [20], who attributed this to the electrochemical potential of the electrode material. Materials with low-electrochemical potential have a low-electrode/electrolyte interface voltage loss.…”
Section: Dewatering and Oil Recovery In The Larger Scale Experimentssupporting
confidence: 90%
“…That study also concluded that the combined effect of applied current intensity and duration is the crucial factor affecting living organisms rather than the current intensity alone. The effect of electrode materials in EK applications using different materials for anode and cathode including steel, copper, and carbon with different combination (anode-cathode) was [83] investigate [75]. The results show that using a particular material as anode and another as cathode or vice versa can result in considerable differences in the electrode performance (efficiency).…”
Section: Electric Current Density and Voltage Gradientmentioning
confidence: 99%
“…Intermittent current was used to avoid the adverse impact of the high temperature [86]. The use of current intermittence not only controls the increase in temperature, but also enhances the outcome of the EK application [75].…”
Section: Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…[2,[17][18][19] In addition to these studies on electrode materials, some other investigations investigated the conduction procedures of electro-osmosis, particularly with regard to polarity reversal and interrupted currents. [20][21][22][23] Furthermore, recent research has also determined that electro-osmotic consolidation can be significantly enhanced in the presence of pre-loading or vacuum loading. [1,[24][25][26] Hence, it is recommended that future applications of electro-osmosis should be coupled with other techniques.…”
Section: Introductionmentioning
confidence: 99%